Pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections - Tan, Jason (College of Family Physicians of Canada, 2012)
Question I have heard about children who have tic disorders that seem to be exacerbated by group A β-hemolytic streptococcal infection. Should children presenting with this phenomenon receive treatment with antibiotics, receive prophylactic treatment, or use immunomodulators to treat the symptoms? Answer Pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections (PANDAS) constitute a condition that includes neuropsychiatric symptoms, mainly obsessive-compulsive disorder or tic disorders, temporally associated with an immune-mediated response to streptococcal infections. The actual existence of PANDAS as a unique clinical entity is still up for debate, as a temporal association between group A β-hemolytic streptococcal infections and symptom exacerbations has been difficult to prove thus far. Based on only a few studies, positive results have been found using antibiotic prophylaxis and immunomodulatory therapy in children with PANDAS. At this time, however, evidence does not support a recommendation for long-term antibiotic prophylaxis or immunomodulatory therapy.